Pigmented purpuric dermatosis type lichen aureus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 18-year-old young man presented asymptomatic brownish lesions on the gluteal region dating from three months. On dermatological examination, there were three patches (Fig. 1), the largest on the left buttock of about 3 x 2 cm, brownish with reddish tinge in the center, a smaller one brownish on the right buttock and a third on the left buttock above the first patch, lighter around a dot-like acquired melanocytic nevus. The presence on dermoscopic observation of red dots in the first and third patch (Fig. 3) led to the diagnosis of pigmented purpuric dermatosis type lichen aureus. At a check-up after 10 months (Fig. 2) the patch of the right buttock was gone, the third smallest patch had become darker while the largest patch was essentially unchanged. At dermoscopy observation persisted the presence of red points both on the largest patch (inset Figure 2) and on the smaller (Fig. 4) that had become darker.